Chemical anchoring of SeS2 on a fluoro-substituted covalent organic framework as a high-performance cathode material. Issue 88 (17th October 2019) - Wang, De-Gao; Wang, Yunyan; Song, Min; Kuang, Gui-Chao; Han, Kai
Abstract : SeS2 is chemically anchored on a fluoro-substituted covalent organic framework and exhibits high electrochemical performance. Abstract : In this work, a high-performance cathode material was achieved by using SeS2 post-functionalization of a fluorinated covalent organic framework (COF) through SN Ar chemistry. The chemical and physical confinement of polysulfides and polyselenides combined with enhanced conductivity boosted its electrochemical performance as a cathode material for lithium–sulfur batteries (LSBs). COF-F-SeS2 delivered a discharge capacity of 1633 mA h g −1 at 0.1C, an excellent C-rate performance of 1163 mA h g −1 at 1C and favorable long cycle performance. This work provides a feasible strategy to overcome the bottlenecks of LSBs for high capacity, excellent C-rate performance and enhanced cycle performance.